(untitled) (Scientific journal of the Fergana State University, 2024)
The article systematizes the analysis of special literature devoted to the influence of physical exercise on the functional state of the body and the content of special theoretical knowledge and practical skills related to the problem in the lifestyle of youth students in our country. Intended for future bachelors, masters, school physical education teachers and sports trainers.